Выявление резервов производства методами статистического моделирования по пассивным данным - Dolgov, Yu. A. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Methods of statistical modeling based on passive data are proposed, allowing the use of accumulated workshop control and measuring information to obtain a model of a specific technological process (operation) suitable for its optimization. A comparative description of the methods is given. The effectiveness of the approach is demonstrated using the example of integrated circuit manufacturing.